PELATIHAN PEMBUATAN ALAT PERAGA FISIKA VIRTUAL BAGI GURU-GURU MUHAMMADIYAH KOTA METRO - Riswanto Riswanto (Jurnal Pengabdian Kepada Masyarakat Sakai Sambayan, 2018)
The learning process must be done by a teacher by making careful planning and use of appropriate learning media. Learning media can be a props or other media that provides an element of ease of delivery of learning information. Observation result with IPA / Physics Teacher Forum Muhammadiyah Metro City shows that only 54.5% of physics teachers in Metro city have used the use of visual aids in learning activities. The facts show that not all existing visual aids can represent all the needs of physics subject matter. Therefore implemented training program given to the muhammadiyah teachers in Metro City includes 3 material that is Urgency virtual props in learning Physics, Training of learning media animation learning IPA / Physics Using Macromedia Flash 8 application, and Use of application tracker (Video Based Learning) as a tool in the activities of science / physics lab. The results obtained show that 89% of teachers feel that the materials provided are in accordance with the needs of teachers today. As many as 75% of teachers feel difficulty in using both software. As many as 83% of teachers feel the facilities provided in the training are sufficient, and as many as 86% of teachers have improved their ability to develop virtual props for science / physics subjects. The follow up of this program is the teachers through whatapps social network can ask and discuss in developing learning media using both applications. Outcomes obtained in this devotion is the publication of devotional information in ISSN's devotional journals and mass media through newspapers and online (website). Keywords: The virtual physics props, Muhammadiyah Kota Metro